Effects of biological and abiotic factors on dark septate endophytes distribution and heavy metal resistance in different environments - Zhenzhou Wang; Wenyi Shi; Xiuling Chen; Yuli Lin; Wenjing Chen; Li Yao; Xiang Sun; Xia Li; Xia Li; Xia Li; Xueli He; Xueli He; et al. (Frontiers in Microbiology)
Graphical abstract